Związki polskiej socjologii wychowania z pedagogiką światową w ostatnim trzydziestoleciu = The connections of Polish sociology of education and world pedagogy in the last 30 years - Leszniewski, Tomasz (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The article presents the state of contemporary Polish sociology of education and show the factors which influenced its development. The first results from the change in the scientific analysis of upbringing and education. In the period after World War II people began to criticize the education and upbringing subordinated to the ideology of the dominant classes and serving primarily the persistence of the same social structure.
Keywords: socjologia wychowania; pedagogika